Pengaruh Live Streaming dan Flash Sale terhadap Impulse Buying melalui Positive Emotion pada Produk Bittersweet by Najla di Platform TikTok Shop - Aleisya Aulia Rachmah; Dita Puruwita; Ivan Putranto (Indo Publishing, 2026)
The rapid development of TikTok Shop through its live streaming and flash sale features has increased impulse buying, which is influenced by consumers' positive emotions. This study aims to analyze the influence of live streaming and flash sales on impulse buying through positive emotion among consumers of Bittersweet by Najla products on TikTok Shop. This study employed a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4. The sample consisted of 130 respondents selected using purposive sampling. The results indicate that live streaming, flash sales, and positive emotion have a positive and significant effect on impulse buying. In addition, live streaming and flash sales also have a positive and significant effect on positive emotion. Furthermore, positive emotion partially mediates the relationship between live streaming and impulse buying, as well as between flash sales and impulse buying. These findings reinforce the Stimulus-Organism-Response (S-O-R) Theory, demonstrating that marketing stimuli can evoke positive emotions that ultimately encourage impulse buying.